Strengthening Student-Supervisor Relationships: An Examination of Postgraduate Students' Perspectives on Supervisory Supports - Adedokun, Theophilus; Oyetunde-Joshua, Funsho (Universitas Negeri Malang, 2024)
This study examined the role of supervisors in supporting postgraduate students from the students’ perspective. Through interviews with postgraduate students at two universities, the research aimed to understand how students perceive and experience guidance from their supervisors. The factors examined included meeting frequency, feedback, and guidance received by students from supervisors. The analysis identified strengths in supervisory support in these areas, as well as areas needing improvement. Results indicated quality feedback and regular communication had the greatest positive impact. However, many students desired more hands-on help with methodology and writing. The study recommends supervisor training programs focused on writing guidance and supervision skills. By implementing such programs, universities can enable supervisors to provide optimal student support, thereby improving experiences and outcomes. This research provides key insights into strengthening student-supervisor relationships